Peran Budaya Organisasi dan Inovasi Dalam Menciptakan Branding Bagi UMKM - METRIS, DIKSI; Ahmad Rasyiddin; Febri Sari Siahaan (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
The study explores the role of organizational culture and innovation in branding for UMKM. In the context of modern business, branding is the key to UMKM to distinguish themselves from competitors, increase consumer confidence, and expand their market share. This article aims to investigate how organizational culture and innovation collaborate to create a strong brand identity for UMKM. Organizational culture has a significant impact on the way UMKM operates and interacts with customers and employees. Innovation in this context involves the innovation of products, processes, and business models that enable UMKM to adapt to changing markets and meet consumer needs effectively. This article also discusses practical strategies that UMKM can adopt to strengthen the culture of organizations that support innovation. This research will use a qualitative approach. The aim of the selection of this approach is to gain a comprehensive and contextual understanding of the dynamics that occur within UMKM organizations as well as how organizational culture and innovation influence the process of branding creation. Research results show that UMKMs who successfully integrate a strong organizational culture with sustained innovation are able to build a consistent branding that attracts consumers. This research provides insights for UMKM owners and business practitioners in understanding the importance of organizational culture and innovation in creating andining competitive advantage through branding.